“Crime and punishment” in the colonies : prosecuting, judging and punishing in colonial Dahomey (1894-1945) - (:unkn) unknown (My University, 2013)
Apprehending the criminal colonial project and placing it in its implementation, from the criminal act or tort to the sanction, throughout prosecution and trial, are the purposes of this research taking place in Dahomey, a French West African territory, between 1894 and 1945. The principle of discrimination between European citizens and Natives on which is built the judicial mechanism extends all along the criminal path, with the perception of a specifically native criminality or the differentiated execution of the penalty according to the convict status. However, this repressive segregated process is not fully considered in its continuity. Whereas native justice is increasingly taken hold of by the colonial government, both ends of the repressive system are not thought of in terms of integration into civil society. The Police and prisons depend on an evolutionary political and economic order. The criminal police and the prison operations are largely left in the hands of local leaders and African auxiliaries, which leads to adjusting the repressive regime into a system of “domination without hegemony”. The backbone of the native justice is at the heart of criticisms against the colonial order, but it is also the place where power relationships are renegotiated and where social conflicts related to the colonial situation are exposed. The criminal path followed by the natives of Dahomey during the first half of the twentieth century appears as the distorted or transformed reflection of a repressive project which is rather formless and dominated by the desire to maintain order.
Keywords: African Research